GROWTH AND NUTRIENT ACCUMULATION BY EICCHORNIA CRASSIPES (MART.) SOLMS IN ROBERTSON LAKE, JABALPUR, INDIA - Jaiswal, Sadhana (Ecoprint: An International Journal of Ecology, 2013)
Macrophytes play an important role in nutrient dynamics of the lake ecosystem. The aim of this study is to determine the growth pattern and to evaluate the nutrient accumulation capacity of water hyacinth [Eichhornia crassipes (Mart) Solms] growing in Robrtson Lake, Jabalpur. The paper is outcome of in situ experiment conducted in Robertson lake (which has a dense mat of water hyacinth), as well as laboratory microcosms experiment. Water hyacinth grew at an average rate of 3.85 g dw m-2d and it accumulates 263 kg N ha-1 yr-1 and 67 kg P ha-1 yr-1, respectively. The chemistry of lake water does not show any significant seasonal variation; however the growth of water hyacinth in laboratory microcosms removed 79% of PO4-P and 58% NO3-N from the growth medium. Thus, the data reveal that water hyacinth stands growing in the lake highly buffered the water chemistry by reducing nutrient level, in spite of heavy nutrient load in the lake from domestic waste and factory effluent. DOI: http://dx.doi.org/10.3126/eco.v18i0.9416 Ecoprint: An International Journal of Ecology Vol. 18, 2011 Page: 91-100 Uploaded date: 12/22/2013